The extended UTAUT model and learning management system during COVID-19: evidence from PLS-SEM and conditional process modeling - Ahmed, Rizwan Raheem; Štreimikienė, Dalia; Štreimikis, Justas (Journal of Business Economics and Management, 2022)
The undertaken research investigates the extended unified theory of acceptance and use of technology (UTAUT) model from the perspective of online education in the deadliest period of COVID-19. This research investigates the extended dimensions, for instance, mobile self-efficacy and perceived enjoyment besides traditional elements of the UTAUT model with the relationship of behavioural intention and user behaviour of LMS. Since the COVID-19 led to social isolation (SIS), thus, this study has incorporated SIS as mediating factor and fear of COVID-19 (FOC) as the moderating factor for the considered extended model of UTAUT. The data of 1875 respondents was collected from five different Asian countries. For the data analysis, this study employed structural equation modeling through PLS-SEM and condition process modeling. This research demonstrates that the extended dimensions such as mobile self-efficacy, besides the traditional elements of the UTAUT model, exerted a cogent impact on behavioural intention except for the perceived enjoyment. Similarly, the behavioural intention demonstrated a substantial effect on the user behaviour of LMS. Additionally, social isolation as a mediating factor and FOC has a significant effect between dimensions of extended UTAUT model and behavioural intention of LMS. The outcomes of this research demonstrate significant theoretical and practical implications during the COVID-19 pandemic. First published online 30 November 2021